2012
DOI: 10.1039/c2cc34399a
|View full text |Cite
|
Sign up to set email alerts
|

New anti-HIV aptamers based on tetra-end-linked DNA G-quadruplexes: effect of the base sequence on anti-HIV activity

Abstract: This communication reports on the synthesis and biophysical, biological and SAR studies of a small library of new anti-HIV aptamers based on the tetra-end-linked G-quadruplex structure. The new aptamers showed EC(50) values against HIV-1 in the range of 0.04-0.15 μM as well as affinities for the HIV-1 gp120 envelope in the same order of magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Later on, Koizumi et al synthesized a set of G-rich oligonucleotides and identified the hexadeosyribonucleotide d(TGGGAG), known as Hotoda’s sequence, [49,50]. Several authors have used the Hotoda’s sequence as a lead sequence to make a series of modifications at the 5′ and 3′ ends of the molecule or mutations in the sequence that allowed to find molecules with high anti-HIV activity [50,51,52,53,54,55,56]. …”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…Later on, Koizumi et al synthesized a set of G-rich oligonucleotides and identified the hexadeosyribonucleotide d(TGGGAG), known as Hotoda’s sequence, [49,50]. Several authors have used the Hotoda’s sequence as a lead sequence to make a series of modifications at the 5′ and 3′ ends of the molecule or mutations in the sequence that allowed to find molecules with high anti-HIV activity [50,51,52,53,54,55,56]. …”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…[11,12] Further factorst hat contribute to the wide polymorphism of G-quadruplexes are the length and the base composition of the loops (when present), as well as the nature of the cationsu sed to stabilize the quadrupleh elix structure. [13][14][15] The biological implications of Gquadruplexes in cellular processes [16][17][18] and their use as promising drugs [19][20][21][22] or in drugs delivery [23] and diagnostics [23][24][25] are well known. In addition, G-quadruplexes possess greater conductivityt han DNA duplexes, thus suggesting their use for the obtainment of electronic nano-biomaterials and nanodevices.…”
Section: Introductionmentioning
confidence: 99%
“…A series of hexadeoxyribonucleotides, carrying various modifications at either the 5′ or the 3′ ends, based on the so called d(TGGGAG) Hotoda's sequence, was also synthesized and evaluated in vitro for their anti-HIV activity, proving to be potent gp120 inhibitors, with IC 50 values from sub-micromolar to nanomolar concentrations [101][102][103][104].…”
Section: Antiviral G4-aptamersmentioning
confidence: 99%